Effect of culture temperature and gaseous phase on embryo development in goat - SINGH, R K; BAG, SADHAN; DAS, B C; MAJUMDAR, A C (The Indian Journal of Animal Sciences, 2011)
The present study was carried out to study the effect of different gaseous phase and culture temperature on in vitro oocyte maturation, fertilization and embryo development in goat. Goa oocytes were matured in TCM-199 with HEPES, 10% FBS, 10% follicular fluid, 0.5 μg/ml FSH, 10 IU/ml LH, 0.5 μg/ml estradiol for 27 h. The mature ooctyes were fertilized with freshly ejaculated sperm in TALP media and cultured in mSOF media without any cell supplementation. The in vitro maturation, fertilization and culture (IVMFC) were done at different gas phases (C1=5% CO2, 20% O2; C2=5% C2, 10% O2; C3=7.5% CO2, 20% O2; C4=7.5% CO2, 10% O2) at 38.5°C as well as 40.5°C in CO2 incubator with maximum humidity. The oocyte maturation rate was 82.78, 87.57, 75.71 and 75.65%, respectively, when oocytes were cultured at C1, C2, C3 and C4 at 38.5°C. The oocyte maturation rate was significantly higher in C2 as compared to C3 and C4. Although there was no significant variation of cleavage rate among the 4 gaseous conditions, it was comparatively higher in C1 (9.44%) as compared to C2, C3 and C4. The development of 4–8 cell and morula stage embryos were also not significantly different among these different gas phases. However, the number of 4–8 cell and morula stage embryos was comparatively higher in C1 condition. The percentage development of 4–8 cell stage embryos was comparatively lower in C4 conditions as compared to C1, C2 and C3. Similarly, the rate of development of morula stage embryos was comparatively lower (1.13%) in C2 condition as compared to C1, C3 and C4. It was also observed that the oocyte maturation rate, cleavage rate and embryo development was lower in 40.5°C as compared to 38.5°C. The present study indicated that alteration of gaseous phase did not have any significant effect on oocytes maturation and embryo development although the maturation rate was significantly higher in 5% CO2 and 10% C2 in goat when oocytes were cultured at 38.5°C. Further it was also observed that higher culture temperature had significantly detrimental effect on the success of IVMFC in goat.